International travel to obtain medical treatment for primary retinoblastoma: A global cohort study. Issue 8 (31st October 2020) - Bowman, Richard J. C.; Foster, Allen; Stacey, Andrew; Keren‐Froim, Naama; Bascaran, Cova; Kivelä, Tero T.; Munier, Francis; Fabian, Ido Didi
Abstract: Early diagnosis and treatment of retinoblastoma (Rb), the most common intraocular malignancy, can save both the child's life and vision. However, access to services and hence chances for survival and preserving the eye and its vision vary widely across the globe. Some families have to, or make a choice to, leave their home country to seek planned medical treatment abroad. We aimed to investigate how frequently this cross‐border travel occurs and the factors associated with it. A total of 278 Rb centres in 153 countries were recruited to participate in a global cross‐sectional analysis of newly diagnosed Rb patients in 2017. Number and proportions of children who travelled from their home country for treatment were analysed by country, continent, socioeconomic stratum and clinical and demographic features. The cohort included 4351 new patients of whom 223 [5.1%, 95% confidence interval 4.5‐5.8] were taken across country borders for planned medical treatment. Independently significant predictors of travelling across borders included: being from a country with a smaller population, being from a country classified as low socioeconomic status, having bilateral Rb and having intraocular disease without extraocular spread. The factors that determine international travel for Rb treatment are complex and deserve further investigation. We may need to rethink the way services are delivered in the light of the threat of severe curtailment of international travel from pandemics like corona virus disease 2019. Abstract : What's new? In most countries, only a single or a few specialized retinoblastoma centres exist. Such a centralization of specialist care may impede access and impose high travel burdens on patients, especially in low‐income countries. Here, the authors report that 5% of a comprehensive global cohort of patients with newly diagnosed retinoblastoma were treated abroad in 2017. This may help save the child's eye and vision but may also delay treatment, a risk exacerbated during pandemics and other crises when international borders are shut down. These findings should promote the coordinated global provision of specialist eye cancer care and emergency travel arrangements.